Predictors of pelvic acceleration during treadmill running at different stride frequencies - James, M. L.; Jones, A. L.; Moore, I. S. (ISBS Proceedings Archive (Michigan), 2022)
The aim of this study was to examine predictors of peak vertical and anteroposterior pelvic acceleration during treadmill running. Participants ran at 9 km·h^(-1) at their preferred stride frequency and at ± 5% of their preferred stride frequency. Coordinate and acceleration data were collected using a motion capture system and inertial measurement units. Linear mixed models showed that for every one standard deviation increase in the anteroposterior displacement from knee to ankle at initial contact, vertical pelvic acceleration increased by 2.18 m·s^2 (p = 0.046). Additionally, for every one standard deviation increase in stride frequency, peak anteroposterior pelvic acceleration increased by 0.68 m·s^2 (p = 0.035). Runners who suffer from injuries or pain at the pelvis may benefit from decreasing the anteroposterior displacement from their knee to their ankle at initial contact and reducing their stride frequency.